Existing bean variability and breeding activities at CIAT for new genetic combinations - Tohme, Joseph M. (Southern Africa Development Coordination Conference (SADCC), 1989)
Assembled germplasm has provided breeders with valuable traits for the improvement of common beans. Molecular markers such as phaseolin and isozymes have facilitated understanding of the genus Phaseolus thus enabling breeders to develop more effective strategies. However, there are still gaps in the collections that have been assembled and in available information. Strategies for conservation need to be coordinated among international and national programs to prevent further genetic erosion of collected germplasm. Duplication of germplasm collections is vital. New sources of genetic variability not present in existing cultivars have been identified and transferred to adapted backgrounds. Wild accessions of P. vulgaris have provided genetic variability and sources of resistance not yet found in cultivated beans. At CIAT, the diversification of sources of resistance to several diseases and insects is well advanced. Broad and stable resistance is being sought. These new resistant sources are deployed through international nurseries which also serve to monitor pathogen variability. (AS)